Two new species of the feather mite genus Dicrurobius Mironov, 2001 (Acari: Astigmata: Pteronyssidae) from drongos (Passeriformes: Dicruridae) in Africa - Mironov, Sergey V.; Wauthy, Georges (Zootaxa, 2005)
Two new species of the feather mite genus Dicrurobius Mironov, 2001 are described from drongos (Passeriformes: Dicruridae) in Africa: Dicrurobius alatus sp. n. from Dicrurus atripennis Swainson, 1837 and D. cameroonensis sp. n. from Dicrurus adsimilis (Bechstein, 1794). New data on host associations and distribution of the sole formerly known species, D. monacrotrichus (Gaud, 1952), are given. A key to three Dicrurobius species known to date is presented.